Efektifitas Rebusan Wortel (Daucus Carota. L) terhadap Penurunan kadar Kolesterol Darah pada Tikus Putih (Rattus Norvegicus) - Misnanto Misnanto; Thatit Nurmawati (Journal of Ners and Midwifery, 2016)
Hypercholesterolemia is a disease of cholesterol metabolism disorder caused by high blood cholesterol. Chemical treatment is reported to have side effects in the long term. The purpose of this study was to determine the effectiveness of carrot stew to decrease cholesterol levels in hypercholesterolemic of rats.The design of this study used experimental randomized control-group pretest - post test design. The samples were divided into control and treatment groups, each group consisted 8 rats. The treatment used a carrot stew with 1.25cc dose and control with medication simvastatin 0144 cc dose was given every morning for 3 days. The measurement of the cholesterol levels used Touch Essey data analysis by Wilcoxon and Mann-Whitney. The study started on May 15th - July 22, 2015.The results of the study showed the cholesterol control group decreased 12.5% (P = 0.069> á = 0.05) in the treatment group and 50% (P = 0.716), On the statistical test showed no effect of carrot stew on blood cholesterol levels. While the results of the effect between treatment and control group (P = 0528> á = 0.05).Carrots with beta-carotene could lower cholesterol levels in the blood, and could prevent the oxidation of Low Dencity Lipoprotein (LDL). The absorption of beta-carotene was better when boiled in temperatures between 60-100 ° C.